Transient Stability Analysis of a Multimachine Power System with TCSC Controller – A Zero Dynamic Design Approach. (April 2018) - Halder, Asim; Pal, Nitai; Mondal, Debasish
Highlights: Zero dynamics design method for design of non-linear TCSC controller for multimachine power system. The efficacy of nonlinear TCSC controller has been presented for different loading conditions. The performance of these nonlinear controllers has been compared with the conventional TCSC controller. The Lyapunov direct stability theorem has been employed to prove the stability of the internal states of the system. The zero dynamic design of nonlinear TCSC controller is more effective than the conventional TCSC controller. Abstract: In this paper a novel non-linear control scheme for Thyristor Controlled Series Capacitors (TCSCs) has been presented to analyze transient stability of a multimachine power system. The non-linear control strategy of the TCSC controller has been formulated by the Zero dynamic design approach. A WSCC type 3-machine 9-bus system has been considered for test system where two numbers of TCSC controllers are placed near the highest load bus in the network. The dynamic stability of the system has been achieved by investigating the stability of the internal states as well as the external states of the system. The stability of the internal states has been ensured by the Lyapunov stability theorem and the external states has been stabilized applying non-linear control law formulated by the zero dynamic design approach. The performance of the non-linear TCSC controller has been compared with its conventional design based on approximate linearization method. The effect of various operating points of non-linear TCSC controller has also been investigated for different loading conditions. The applicability of the above nonlinear control scheme is further demonstrated for a large power system comprising 14-areas, 24-machines and 203-buses. The simulation results for all the cases have been presented through time domain simulation of the proposed test systems with application of typical contingency and different loading conditions. It has been observed that the non-linear control scheme for the TCSC controller is more effective compared to its conventional design as well as its performance is quite satisfactory for different loading conditions in mitigating transient stability of a multimachine power system.